Conscious sedation in child patient management - Pil, Adonis T. (The Journal of the Philippine Dental Association)
Conscious sedation has been defined as a minimally depressed level of consciousness that retains the patients' ability to maintain airwa independently, continuously and respond appropriately to phusical stimulation and verbal command.